Mobilitas Ekonomi Pra Pasca Pandemi Covid 19: Masyarakat di Kawasan Wisata Kawah Wurung Kabupaten Bondowoso - Fatihatul Firdaus; Lusiana Agustiningtiyas (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2023)
Covid-19 pandemic has changed economic conditions as experienced by the communities in the tourism area of the Wurung Crater. The number of tourist visits that greatly determine their daily income affects their current economic condition. The pre- and post-Covid-19 pandemic economic mobility among the communities in the tourism area of the Wurung Crater has become the main cause or factor for the decline in community welfare. In conducting this research, the researcher used qualitative method. The data were obtained through observation, interview, and documentation. The research was conducted around the Wurung Crater tourism area, Bondowoso Regency, with the aim of gaining and digging information regarding the condition of the communities around the tourism area of the Wurung Crater before and after the Covid-19 pandemic. Data analysis was carried out to determine the effect of the Covid-19 pandemic on several aspects and connect it to the social mobility theory which includes economic mobility. In addition, the analysis was also carried out to find out several other influences that have caused the communities to switch jobs or even have various other side jobs. It was known that it influences the economy and the post-pandemic condition of the communities in the Wurung Crater tourism area.